SAMPLING PROTOCOLS FOR FOREST AERIAL SURVEY IN COLORADO, US - Quang Anh, Ha; The Doi, Bui; Minh Toan, Pham (Journal of Forestry Science and Technology, 2016)
Aerial sketch-mapping is a common technique that has been used to estimate the extent and severity of observe damaged forest from an aircraft. In Colorado State, data on forests survey by aircraft using sketch-mapping has been collected from 1994 until now. Because of very large data has been collected each year so it is difficult and takes time and cost of money. Choosing appropriate sample designs to estimate for population estimators is necessary and economical.In this paper, three sample designs (Simple Random Sampling - SRS, Systematic Sampling - SYS, and Probability Proportion to Size - PPS) with different sample sizes were conducted and compared to find the best and applicable one to the reality of forest management. The comparing is conducted by doing simulation with 20,000 times for each sample design and based on the values of some important estimators between sample designs and the population’s values. The biased and unbiased characteristics of estimators are considered as the main evidences for conclusions.